Análise da importância da questão participativa dos recursos hídricos no Ceará: um estudo de caso - Silva, Ubirajara Patricio Alvares da (2004)
The water is a renewable natural resource, basic for the life in the planet, presenting the characteristic to be always in movement in its hydrologic cycle. The current situation of ambient crisis in the world has contributed strong for the increase of the scarcity of the water. The increase of the demand and the conflicts for the use of the water places the necessity of the management participatory of the water resources, understanding the water public property. This research aims at to analyze the importance of the management participatory of the water resources in the Ceará, and of that it forms the implementation of the State Water Resources Policy contributes in the process of allocation and conservation of the water, for the sustainable development in the Water Basin of the Curu. This analysis approaches the question ambient; the principles and models water management; the development institutional for the water management; the relative aspects to the management participatory of the water and the performance of the water basin committee of the Curu. Given the complexity of the subject, is essential an interdisciplinary approaches, for the necessity to argue the some elements that if interpose in the understanding of the ambient question and the water resources. For this it is necessary to contemplate the aspects of the totality and historic. Interviews had been carried through, with the members of the water basin committee of the Curu and also the presidents of the public agencies of the management system: COGERH, SOHIDRA and FUNCEME. The water management, understood while a public policy, must have as basic principle the participation accomplishes of the society in the planning and deliberation concerning its use and conservation, which had to be an element essential the life and to be public property, whose allocation must socially be joust, ecologic sustainable and economically viable, being party to suit of sustainable development. During the development of the research searched to work a bigger agreement and definition of concepts keys that we consider important, such as: Society/Nature, Ambient Management, Sustainable Development, Management of the Resources water and Social Participation.